There is no hero in heroin : one mom's journey to finding the hero within herself, despite her son's addiction - Nargi, Janice M. (Tucson, AZ : Twin Feather Pub., 2012)
Jan Nargi, a single mother of two, is a registered nurse who worked in enough emergency rooms to know the signs of addiction, but failed to recognize them in her own family. Her son, Tommy, is a heroin addict. He started abusing Oxycontin when he was sixteen and graduated to mainlining heroin by age eighteen. This is their story. The one of his life chasing the high, and her life chasing after him. They hope their collaboration will strengthen their relationship, assist Tommy on the road to recovery, and offer help and encouragement to others struggling with the battle of addiction. They pray their story will convince you to chase a new high, a natural high on life. This story is factual. It is graphic. It is real. There is no hero in heroin.
Keywords: Heroin abuse -- Patients -- Family relationships; Drug addicts -- Family relationships; SELF-HELP -- Substance Abuse & Addictions -- Drug Dependence; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; Drug addicts -- Family relationships; Electronic books; Electronic books